The construction of women position in sport: a textual analysis of articles and images on female athletes in Malaysian dailies newspapers during 26th sea games 2011 / Siti Amirah Haji Amiruddin - Amiruddin, Siti Amirah (2016)
Sport media is seldom covered women’s athletes by excluding them from sports news. Yet, female athletes often to be compared between male athlete’s ability and hegemonic powers during sport media coverage. This study identifies how national printed media in Malaysia (New Straits Times and Berita Harian) provides coverage to female athlete’s performance and also analyse construction of empowering positions and disempowering positions for women especially in newspapers. Methods: a content analysis is used to determine the descriptor in the newspaper’s content of both newspapers based on articles and images in sport sections during 26th Sea Games 2011 at Indonesia. Kian [2008] coding system was used to analyse the articles and Sport Illustrated Content [1997-2000] coding system for images. Result: Both of newspapers shows the different angle of View for women athletes where the highest numbers of articles published by Berita Harian focusing on psychological strengths and emotional strengths while New Straits Times is focusing on the positive skills level and accomplishment. However, both newspapers give a lowest coverage of articles which was focusing on athletic weaknesses and limitations. Instead, there is no coverage for humor and physical appearance, sexuality and attire. For images, NST and Berita Harian focused on the same coded of portrayal for non-sport setting images rather than athletic action. Yet, both newspapers also not even portrayed images on pornographic/sex-appropriate and dress but poised and pretty.